Detailed Metabolic Characterization of Flowers and Hips of Rosa gallica L. Grown in Open Nature - Nina Kunc; Metka Hudina; Maja Mikulič-Petkovšek; Jože Bavcon; Blanka Ravnjak; Gregor Osterc (Plants, 2023)
Our research aimed to investigate the primary and secondary metabolites of rosehips and petals of R. gallica in comparison with R. subcanina. R. gallica was chosen because it is still unexplored in terms of various bioactive substances and is strongly present in Slovenia. Given that roses are generally very variable and unstudied, our research will contribute to greater transparency and knowledge of the bioactive composition of rosehips and petals. We found a strong positive correlation between the total content of phenolics and ascorbic acid, between the total content of organic acids and the total content of carotenoids, and between the total content of sugars and the total content of organic acids. Hips of R. gallica contained higher amounts of sugars, ascorbic acid, and carotenoids than R. subcanina. Based on the composition of phenolic compounds in the petals, it is possible to distinguish between the two species. Among all the phenolic compounds in the petals, both genotypes are richest in gallotannins, followed by flavonols. Among anthocyanins, cyanidin-3-glucoside was determined, the content of which was also higher in R. gallica. It can be concluded that the studied hips had an extremely low sugar content and, consequently, an extremely high organic acid content. The content of carotenoids in hips was in the lower range of the average content compared to data from the literature. By optimizing the harvesting time, we could obtain a higher content of carotenoids, which could potentially be used for industrial purposes. However, we found that the analyzed petals were a rich source of phenolic compounds, which benefit the human body and could be potentially used in the food and cosmetic industries.